Ijtihad Berbasis Maqashid Syari’ah Sebagai Pijakan Konseptual Dalam Pembaruan Hukum Keluarga Islam Indonesia - Tohari, Ilham; Kholish, Moh. Anas (Jurnal Hukum & Pembangunan, 2023)
Many circles consider that Islamic family law in Indonesia must be renewed. But Islamic family law renewal is not an easy matter. The rejection of various parties to the Counter Legal Draft-Compilation of Islamic Law (CLD-KHI), as an effort to renew Islamic family law, become evidence of the difficulty of the renewal. Rejection of the CLD-KHI on the other hand also shows that Islamic family law reform must be carried out with approaches and methodologies derived from the tradition of Islamic thought itself. In this context, ijtihad based on maqashid syari'ah acts as a conceptual basis for the methodology of Islamic family law reform. This article aims to examine how the formulation and methodological contribution of maqashid syari'ah-based ijtihad in the development of Islamic family law. This study is normative juridical with a statute approach and analytical approach. The analysis is carried out with a qualitative descriptive method to describe the methodological contributions of ijtihad based on maqashid shari'ah in the formulation and development of Islamic family law.